Pengaruh Ekstrak Gel Daun Kemangi (Ocimum Sanctum L.) terhadap Re-Epitelisasi Luka pada Proses Penyembuhan Luka Post Ekstraksi Gigi Tikus Wistar (Rattus Norvegicus) - Gedu, Sebastiani Alichia; Asmarani, Yolanda (Bhakta Dental Journal, 2025)
Background: Tooth extraction is a surgical procedure to remove a tooth from the alveolar bone socket, which can cause trauma or injury to the tissue around the tooth. One of the wound healing processes after tooth extraction is the proliferation phase, in this phase the re-epithelialization process occurs. Basil leaves (Ocimum sanctum L.) contain chemical compounds that can accelerate the wound healing process, have an antioxidant effect that can accelerate the inflammatory phase and prevent oxidation reactions by increasing the activity of the enzymes Superioxide Dismutase (SOD) and glutathione s-transferase. Objective: This study aims to determine the effect of basil (Ocimum sanctum L.) leaf gel extract on increasing wound re-epithelialization in the wound healing process post-tooth extraction of Wistar rats (Rattus norvegicus). Methods: This study used an experimental laboratory design in vivo, with a posttest only control group design. The samples used were 32 Wistar rats (Rattus norvegicus) divided into control groups and treatment groups of basil leaf gel extract (Ocimum sanctum L.) with a concentration of 1.5%. Results: The Mann- Whitney significance value in the results of this study was 0.378. Asymp significance 0.378 > 0.05 states that there is no real or meaningful difference from the measurement results between the control group and the treatment group. Conclusion: There is no significant difference from the measurement results between the control group and the basil (Ocimum sanctum L.) leaf extract gel treatment group with a concentration of 1.5% on increasing the re-epithelialization of wistar rat post-tooth extraction wounds (Rattus norvegicus) . Keywords: Tooth extraction, wound healing, basil leaf extract (Ocimum sanctum L.)